Multidrug-Resistant Escherichia coli Resulting in Postpartum Necrotizing Endomyometritis - Joan Tymon-Rosario; Meleen Chuang (Case Reports in Obstetrics and Gynecology)
Background. Postpartum endometritis is a fairly common postoperative complication occurring in up to 11 percent of all cesarean deliveries. Multidrug-resistant pathogenic organism is increasingly a factor in postoperative source of infection. Postpartum endomyometritis from a multidrug-resistant Escherichia coli infection resulting in uterine is one such rare clinical circumstance where there is minimal information in the literature to guide its treatment and management. Case. A 29-year-old G1P0 who underwent a primary cesarean delivery for a failed induction of labor developed endomyometritis on post-op day one and was treated with multiple broad-spectrum antibiotic regimens. The source of infection was found to be multidrug-resistant Escherichia coli with uterine involvement and pelvic abscesses, requiring hysterectomy and drainage of pelvic abscesses. Severe uterine necrosis from this multidrug-resistant Escherichia coli infection was noted intraoperatively. After three weeks of antibiotic therapy, she had resolution of her infection. Conclusion. Multidrug-resistant Escherichia coli is a highly pathogenic organism that can cause endomyometritis, persistent bacteremia, and uterine necrosis, which necessitates definitive surgical management with hysterectomy to achieve resolution of the infection.